Clinical profile and underlying causes of recurrent pneumonia in children: a hospital based study - Bhadra, Shima; Rahman, M. Atiar; Akter, Sajeda (International Journal of Contemporary Pediatrics, 2025)
Background: Recurrent pneumonia (RP) remains a challenge for the pediatrician. There are limited data on RP specially in developing countries. Identification of underlying cause of RP is crucial for managing the patients. Methods: This retrospective study was conducted in pediatric pulmonology ward of Bangladesh medical university from January 2023 to December 2024 to observe the clinical profile and to recognize the underlying causes of RP in children. Total 65 undiagnosed cases of RP children aged 1 month to 18 years were enrolled in this study. Results: Out of the 253 children with pneumonia around 26% had experienced recurrent episodes. Most of the patients presented before the age of 6 months. Cough was present in 65 (100%), fever in 60 (92.3%), followed by breathing difficulty in 50 (76.9%). Tachypnea was observed in 39 (60%), crackles in 43(65.07%) and wheezing in 13 (17.4%) cases. A considerable number, 85.7% belonged to low socioeconomic class. Leukocytosis (55%) and raised ESR (64.6%) were the most common lab findings. Bronchopneumonia (40%) was the common findings in chest x-ray and in CT scan consolidation (39.02%) followed by interstitial pneumonitis (29.2%) were the predominant findings. Underlying causes were detected in 92% cases, of which most predominant causes were cystic fibrosis (35.3%) followed by congenital heart disease (CHD) (16.9%) and congenital airway disease (12.3%). Conclusions: Cystic fibrosis was the predominant underlying cause followed by CHD and congenital airway abnormality. Children of RP should be carefully evaluated for cystic fibrosis and CHD.